FASILITAS KREDIT DAN E-COMMERCE DALAM PERKEMBANGAN UMKM PADA UMKM JAKPRENEUR KECAMATAN KRAMAT JATI - Agustina, Nadya; Mukhtar, Saparuddin; Saptono, Ari (Yayasan Education and Social Center, 2023)
The situation after being hit by the pandemic in the previous year resulted in many MSME players deciding to close their businesses as a result of decreasing business income. Apart from the pandemic, there is another problem that often becomes an obstacle for MSMEs to develop, namely capital. MSMEs are a type of micro and small business where most of the capital comes from individual business owners so of course they have a limited amount. On the other hand, problems such as low knowledge of Human Resources are related to the world of business and technology. The aim of this research is to determine the effect of utilizing credit facilities on business development in Jakpreuner MSMEs in Kramat Jati District. The research results show that the variables Utilization of Credit Facilities, Use of E-Commerce partially influence the development of Jakpreuner MSMEs. Utilization of credit facilities and use of E-Commerce have had a substantial impact on the development of Jakpreuner MSMEs. Apart from that, the coefficient of determination shows that the use of credit facilities and the use of E-Commerce all contribute to the development of Jakpreuner MSMEs in Kramat Jati District by 69.5%, while the remaining 30.5% is influenced by other variables